1999
DOI: 10.1590/s0041-87811999000300003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperbaric oxygen on the regeneration of experimental crush injuries of nerves

Abstract: SUMMARY: Hyperbaric oxygen has been successfully used on treatment of acute ischemic injuries involving soft tissues and chronic injuries. In nerve crush injuries, the mechanisms involved are very similar to those found in ischemic injuries. Consequently, it is logical to hypothesize that hyperbaric oxygen should improve nerve repair, which is a critical step on functional recovery. In the present study, we created standard nerve crush injuries on sciatic nerves of rats, which underwent treatment with hyperbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The minimum HBO dose required to achieve those effects has not been established. When using HBO‐treatment periods less than half those used by Tuma Junior et al (1999) , no effect was found on SFI of HBO treatments following rat sciatic nerve crush injury and nerve transection and repair. Our study shows that the morphological effects are not followed by an effect on the restoration of either the gait or the muscle force in reinnervated muscle.…”
Section: Discussionmentioning
confidence: 93%
“…The minimum HBO dose required to achieve those effects has not been established. When using HBO‐treatment periods less than half those used by Tuma Junior et al (1999) , no effect was found on SFI of HBO treatments following rat sciatic nerve crush injury and nerve transection and repair. Our study shows that the morphological effects are not followed by an effect on the restoration of either the gait or the muscle force in reinnervated muscle.…”
Section: Discussionmentioning
confidence: 93%
“…An additional five case reports describe a total of two female and three male patients, aged 24–50, treated with HBOT for PNI (table 2). 20 21 30–32 The remaining 40 studies, which are illustrated in table 3, describe experiments performed in a rat model,33–70 with the exception of two which used a rabbit model 71 72. Collectively, they chronicle more than 800 animal models of HBOT for the treatment of PNI.…”
Section: Resultsmentioning
confidence: 99%
“…Four human trials describe PNI of the ulnar and median nerves,24 sural and peroneal nerves,25 pudendal nerve,27 and brachial plexus,28 while the remaining human studies describe patients with variable or widespread nerve injuries such as complex regional pain syndrome or distributed peripheral neuropathies (table 1 and table 2). 20 21 26 29–32 Among animal studies (table 3) the most common nerve of interest (in 28/40 studies) is the sciatic nerve,33 37 41–44 46–56 58 60–64 66–68 70 72 while others examine the L5 spinal nerve,38 45 57 peroneal nerve,65 69 or cavernous nerve 59. Several additional animal studies describe distributed peripheral neuropathies 34–36 40 71…”
Section: Resultsmentioning
confidence: 99%
“…However, Haapaniemi et al who used a protocol for HBO treatment similar to Zamboni et al reported that HBO treatment does not affect nerve recovery. When less than half those HBO‐treatment periods were used by Tuma Júnior et al, no effect of HBO treatments was found on SFI. There was no effect on early diabetes nerve damage .…”
Section: Discussionmentioning
confidence: 96%